2018
DOI: 10.5505/yeditepe.2018.99608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the knowledge, experience and gender influence on the shade matching

Abstract: Anahtar kelimeler: Renk, renk seçimi, cinsiyet, tecrübe, Toothguide Training Box. SUMMARY Aim:The purpose of this study was to evaluate the influence of color education, gender and level of experience on shade matching quality. Materials and Methods: A study was simultaneously performed a total of 218 color normal participants who were dental students and prosthodontic post-graduate students. A lecture on color and color matching in dentistry was given to half of the dental students. Post-graduate students wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…28 In the current research, the result showed that gender had no statistically significant effect on shade matching. This result is similar to the study findings of Alfouzan et al, 21 Erzincanlı and Kazazo glu, 23 and Aswini et al 27 In addition, the result of the present research corresponds with the study of Negahdari et al 4 who compared shade matching using two shade guide systems of Vitapan Classical and 3D Master by dental students. The cited study reported that there was no significant difference between the two genders, but males exhibited higher results when the Vitapan Classical shade guide was used and females exhibited better results by using the 3D Master system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…28 In the current research, the result showed that gender had no statistically significant effect on shade matching. This result is similar to the study findings of Alfouzan et al, 21 Erzincanlı and Kazazo glu, 23 and Aswini et al 27 In addition, the result of the present research corresponds with the study of Negahdari et al 4 who compared shade matching using two shade guide systems of Vitapan Classical and 3D Master by dental students. The cited study reported that there was no significant difference between the two genders, but males exhibited higher results when the Vitapan Classical shade guide was used and females exhibited better results by using the 3D Master system.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of the visual‐instrumental shade agreement scores was significantly higher for clinically experienced dentists. Furthermore, Erzincanlı and Kazazoğlu, 23 evaluated the effect of color knowledge, gender, and experience on the quality of shade matching. The results showed that examiners with basic color knowledge matched the shades more successfully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation